Capaian Indikator Kesehatan Ibu dan Anak pada Pendekatan Program Indonesia Sehat–Pendekatan Keluarga (PIS-PK) di Desa Lambuluo, Kabupaten Konawe Utara - Handayani, Listy (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Maternal and Child Health (MCH) is a priority domain of the Healthy Indonesia Program with a Family Approach (PIS-PK). This study aims to describe the achievement of PIS-PK indicators in the MCH domain in Lambuluo Village, North Konawe Regency. This research employed a descriptive observational method with a cross-sectional design. Data were collected in January 2025 using questionnaires administered to all heads of households through a total sampling technique, involving 76 households. The collected data were processed and analyzed using univariate analysis. The achievement of MCH indicators included family planning participation (56.7%), childbirth in health facilities (59.7%), exclusive breastfeeding (53.7%), monitoring of under-five children’s growth at integrated health posts (64.2%), and complete basic immunization coverage (62.8%). Overall, the achievement of these indicators was not yet optimal, particularly in exclusive breastfeeding, delivery in health facilities, completeness of immunization, and growth monitoring. The findings of this study can serve as important input for planning family-based follow-up interventions through strengthening maternal counseling and assistance, implementing outreach strategies for integrated health post services and immunization, as well as improving access to health services and referral systems at primary health centers.